Obeticholic Acid and Fibrates in Primary Biliary Cholangitis: Comparative Effects in a Multicentric Observational Study. (23rd November 2021) - Reig, Anna; Álvarez-Navascués, Carmen; Vergara, Mercedes; Gómez-Domínguez, Elena; Gallego-Moya, Adolfo; Pérez-Medrano, Indhira M.; Fábrega, Emilio; Hernández-Guerra, Manuel; Berenguer, Marina; Estevez, Pamela; Arencibia, Ana; Morillas, Rosa M.; et al.
Abstract : INTRODUCTION: Obeticholic acid (OCA) and fibrates therapy results in biochemical improvement in placebo-controlled trials in patients with primary biliary cholangitis and insufficient response to ursodeoxycholic acid. There is scarce information outside of clinical trials. Therefore, we have assessed the effectiveness and adverse events of these treatments. METHODS: Data from patients included in the ColHai registry treated with OCA, fibrates, or both were recorded during a year, as well as adverse events and treatment discontinuation. RESULTS: Eighty-six patients were treated with OCA, 250 with fibrates (81% bezafibrate; 19% fenofibrate), and 15 with OCA plus fibrates. OCA group had baseline significantly higher alkaline phosphatase (ALP) ( P = 0.01) and lower platelets ( P = 0.03) than fibrates. Both treatments significantly decreased ALP, gamma-glutamyl transferase (GGT), and transaminases and improved Globe score. Albumin and immunoglobulin type M improved in the fibrates group. ALP decrease was higher under fibrates, whereas alanine aminotransferase decline was higher under OCA. Although baseline transaminases and GGT were higher in patients with OCA plus fibrates, significant ALP, GGT, alanine aminotransferase, and Globe score improvement were observed during triple therapy. Adverse events were reported in 14.7% of patients (21.3% OCA; 17.6% fenofibrate; 10.7% bezafibrate), mainly pruritus (10.1% with OCA). Discontinuation was more frequent in fenofibrate treatment mainly because of intolerance or adverse events. DISCUSSION: Second-line therapy with OCA or fibrates improves hepatic biochemistry and the GLOBE score in primary biliary cholangitis patients with suboptimal response to ursodeoxycholic acid. Simultaneous treatment with OCA and fibrates improved ALP as well.